Proceedings of SPE International Symposium on Oilfield Chemistry 1995
DOI: 10.2523/28993-ms
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Modelling for Prediction of Asphaltene Deposition in Live Oils

Abstract: This papar w selactad for presentation by an SPE Program Committae Iollowlng raviaw of infwmatlon wntainad in an abstraclsubmfttad by the author(s). Contents of the papar, = Pfe-td, heve not bwn revwad by the SOCIatYof Petrcieum Engineers and ara sut@t to correction by IF+Sauthcf(s). Tha materhl, as prasented. does not nacassarily raftect any position of the Scdefy of Petroleum Enginaars, its officers, w mambam. Papain prasentad at SPE maetin@ are subjact to publication revfaw by Ednorfal Commtiaaa of tha Soc@… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
53
0

Year Published

1996
1996
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(57 citation statements)
references
References 1 publication
4
53
0
Order By: Relevance
“…In order to examine the capabilities of the models reported in the literature to predict asphaltene phase behavior in dilute systems, Cimino et al [2,14] (Table 1) to find onset of precipitation of dissolved asphaltenes in various solutions with different ratios of solvent and precipitant and indicated that the precipitated asphaltene does dissolve in appropriate solvent and the ratio of "solvent mass per asphaltene mass" and "precipitant mass per asphaltene mass" is approximately linear and independent of the asphaltene concentration at onset of asphaltene precipitation [2,14]. They showed that the capability of colloidal model [25] and traditional Flory-Huggins [36] based models [8,20] to re-produce the observed behavior is poor, mainly because most of the models reported in the literature assume that the precipitated phase consists of asphaltene only and the presence of non-asphaltene components in the precipitated phase is normally ignored.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In order to examine the capabilities of the models reported in the literature to predict asphaltene phase behavior in dilute systems, Cimino et al [2,14] (Table 1) to find onset of precipitation of dissolved asphaltenes in various solutions with different ratios of solvent and precipitant and indicated that the precipitated asphaltene does dissolve in appropriate solvent and the ratio of "solvent mass per asphaltene mass" and "precipitant mass per asphaltene mass" is approximately linear and independent of the asphaltene concentration at onset of asphaltene precipitation [2,14]. They showed that the capability of colloidal model [25] and traditional Flory-Huggins [36] based models [8,20] to re-produce the observed behavior is poor, mainly because most of the models reported in the literature assume that the precipitated phase consists of asphaltene only and the presence of non-asphaltene components in the precipitated phase is normally ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Scatchard-Hildebrand [7], Flory-Huggins [7,36], and Scott-Magat [37] polymer solution theories) to model phase behavior of asphaltenecontaining fluids [1,2,5,7,8,14,[20][21][22][23]. In addition to these models, there are also other models, which are based on cubic equations of state [17,24].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations